A narrative review of digital storytelling for social work practice. Issue 1 (2nd January 2021) - Chan, Chitat; Sage, Melanie
ABSTRACT: Digital storytelling (DST), broadly defined, is a storytelling method that is interwoven with digitised images, texts, sounds, and other interactive elements, and it has been increasingly used for social work and healthcare interventions. While the term DST has become more popular, its role in actual social work interventions is not clear. The ambiguity of DST presents a hurdle to further theorisation for social work practice and research. This article aims to provide a narrative review and derive a conceptualisation that is in line with social work's psychotherapeutic and systems orientation. The review has derived a two-layer conceptualisation. In a broad sense, DST can be seen as an umbrella term covering different sorts of storytelling activities that use digital communication media. Practitioners and researchers can adopt a set of parameters for describing and comparing different practice designs. More specifically, DST can be seen as a kind of narrative practice utilising digital communication media. This definition offers a conceptual base for DST, which helps further theorisation and research in social work practice.